Communicating to the Ages: Influence of Age on Florida Residents’ Informational Processing Behaviors - Amanda D. Ali; Laura A. Sanagorski Warner; Ashley N. McCleod; Shelli Rampold; Alexa J. Lamm (EDIS)
This 5-page document explores the results of a study in which Florida residents processed video messages about fertilizer best practices, with a focus on how their information-processing behaviors differed by age. Written by Amanda D. Ali, Laura A. Sanagorski Warner, Ashley N. McCleod, Shelli Rampold, and Alexa J. Lamm and published by the UF/IFAS Department of Agricultural Education and Communication, December 2018. http://edis.ifas.ufl.edu/wc323